Teaching Work and Structural Inequalities during the COVID-19 Pandemic - Moreno Ortiz, Magdalena (Sekkan Revista de Ciencias Sociales y Humanidades, 2026)
This article analyzes the labor impacts experienced by basic education teachers in Tamaulipas, Mexico, during the COVID-19 pandemic. The objective is to understand how the health crisis reshaped teaching work, depending on the geographic context (rural or urban) and the sex of the teaching staff. A mixed-methods approach was used: an online questionnaire was applied to 1,035 teachers and 14 semi-structured interviews were conducted. Quantitative data were analyzed using Chi-square and Fisher’s exact tests, while qualitative data were thematically coded. The analysis draws on a critical perspective that incorporates insights from the sociology of education and gender studies to understand structural inequalities in teaching work. Results show that more than 90% of teachers reported labor-related impacts, particularly increased workload, normative ambiguity, and administrative pressure. Although no statistically significant differences were found, qualitative data reveal unequal conditions: in rural areas, technological limitations led to face-to-face strategies without institutional support, and female teachers faced a triple workload across pedagogical, administrative, and domestic tasks.